Performance evaluation of airline companies from consumers’ perspective based on topsis and vikor methods - Çetinkaya, Sümeyye (My University, 2019)
Günümüzde artan teknoloji ve küreselleşmenin etkisiyle havayolu taşımacılığı ciddi bir önem kazanmıştır. Artan bu talep doğrultusunda her geçen gün rekabet daha da artmaktadır. Havayolu pazarında kendine yer bulmak ve rekabette güçlü olmak için, firmaların tüketici ihtiyaç ve isteklerini göz önünde bulundurmaları en birincil şartlardandır. Sürekli değişen ve gelişen bu sektörde yalnızca teknik bağlamda ilerlemek tek başına yeterli olmayacaktır. Merkezinde “insan” olan bu sektörde müşteri isteklerini dikkate almak kaçınılmazdır. Havayolu taşımacılığı, iş seyahati, turistik gezi, eğitim-öğretim gibi birçok farklı sebepten ötürü tercih edilmektedir. Değişen lüks algısı ve artan tüketici hakları bilinciyle müşteriler kurumsallık, uçak içi hizmetler, uçak içi konfor, ulaşım, bekleme süresi, fiyat, güvenilirlik ve tanınırlık gibi birçok kritere dikkat etmektedir. Havayolu şirketlerinin sürekli artması demek, hem rekabetin artması demek, hem de müşteri için daha fazla kıyas yapma imkânı demektir. Uçmak için farklı şirketleri kullanan müşteriler, firmaları kıyaslayacak ve bu kıyaslama sonucunda da kendi kriterlerine en çok uyan firmayı tercih edeceklerdir. Bu durumda firmalara düşen görev, müşterilerin kriterlerini doğru tespit etmek ve bu tespit doğrultusunda iyileştirmeler yapmaktır.Bu bağlamda, bu çalışmada ilk hedef, Analitik Hiyerarşi Süreci (AHP) kullanarak müşterilerin havayolu şirketi seçerken hangi kriterlere hangi ölçüde dikkat ettiğini bulmaktır. Çalışmanın devamındaki amaç ise, TOPSIS ve VIKOR yöntemleri kullanılarak, karşılaştırmalı olarak bu kriterler doğrultusunda tüketicilerin en çok hangi havayolunu tercih ettiğini bulmaktır.

Nowadays, due to the increasing technology and globalization, air transportationas gained serious importance. Due to increasing demand, the competition is increasing day by day. In order to increase the market share and continue sustainable development in the airline market and to be strong in the competition, the airline market and to be strong in the competition, it is one of the primary requirements that companies take into account consumer needs and wishes. In this constantly changing and evolving sector, advancing in the technical context alone will not be enough. It is inevitable to take into account customer requests in this sector which is “humankind” in its center.Air transportation is preferred for many reasons such as business travel, touristic trips, education and training. With the perception of changing luxury and increasing consumer rights, customers pay attention to many criteria such as corporate, in-flight services, in-flight comfort, transportation, waiting time, price, reliability and recognition. A continuous increase in airline companies means both increasing competition and providing more comparisons for customers. Customers who use different companies to fly will compare companies and will prefer the company that best fits their own criteria as a result of this comparison. In this case, the task of the firms is to determine the criteria of the customers correctly and to make improvements in this direction.In this case, the first objective in this study is to rank criteria which have a role in selecting the airline company by customers using the Analytic Hierarchy Process (AHP). And the later aim of the study is to find out which airline preferred the most by using TOPSIS and VIKOR methods.The importance of the criteria according to the results obtained by AHP method is as follows: reliability(safety factor), timing, number of flight points and aircraft, corporate image and public recognition, ticket prices, in-cab comfort and convenience andin-flight service quality. The most preferred airline company is determined according to TOPSIS and VIKOR methods.
Keywords: AHP; Airline Companies; Business; Customer Criteria; Customer Satisfaction; Çok Kriterli Karar Verme; Decision making; Havayolu Taşımacılığı; İşletme; Karar verme; Multi Criteria Decision Making; Müşteri Kriterleri AHP; Müşteri Memnuniyeti; TOPSIS; VIKOR